Analisis Kinerja Keuangan Pt Indofood Sukses Makmur TBK - Dianizar El Ghifari; Muhammad Bukhori; Azy Nugraha; Istiono Istiono (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to analyze the financial performance of PT Indofood Sukses Makmur Tbk during the 2020–2024 period using financial ratio analysis and the Economic Value Added (EVA) method. The research was conducted because Indofood, as one of the largest consumer goods companies in Indonesia, faces challenges related to global economic uncertainty, fluctuations in raw material prices, and changes in consumer purchasing power. The research method used is descriptive quantitative with secondary data obtained from the company’s annual reports and related journal articles. The analysis was carried out through liquidity, solvency, profitability, activity ratios, and EVA to measure the company’s ability to create economic value. The results indicate that Indofood has a very strong liquidity level with a Current Ratio of 2.15 times in 2024. The solvency ratio also reflects a healthy financial condition with a Debt to Equity Ratio of 0.85 times. The company’s profitability improved, as indicated by the increase in net income and EBIT by 17% in 2024. However, asset utilization efficiency still needs optimization because the activity ratio has not fully met industry standards. Overall, Indofood successfully maintained financial resilience and stability amid global economic uncertainty.